2010
DOI: 10.1130/b30017.1
|View full text |Cite
|
Sign up to set email alerts
|

Suprasubduction-zone ophiolite generation, emplacement, and initiation of subduction: A perspective from geochemistry, metamorphism, geochronology, and regional geology

Abstract: Ophiolites are on-land remnants of oceanic lithosphere, and most of the more extensive ophiolites apparently formed above a subduction zone, a tectonic setting known as a suprasubduction-zone setting. Thin sheets of high-grade metamorphic rocks, known as metamorphic soles, crop out structurally beneath many suprasubduction-zone ophiolites. Such rocks may have formed during the inception of subduction beneath young and hot oceanic lithosphere. Disagreement exists as to whether suprasubduction-zone ophiolites ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(57 citation statements)
references
References 97 publications
2
55
0
Order By: Relevance
“…Sierra Nevada ranges (Dunne et al 1998;Irwin 2003;Dickinson 2008) reflects an important component of eastward subduction of the Farallon oceanic plate commencing no later than *175 Ma, and continuing until *140 Ma. Underflow also resulted in the generation and storage at depth of HP/LT metamafic rocks, now present as tectonic ± olistostromal blocks in mélanges chiefly of the Franciscan Central Belt (Cloos 1982(Cloos , 1986Wakabayashi et al 2010). Middle and Late Jurassic oceanic plate motion probably involved oblique convergence rather than nearly orthogonal subduction ), because if a major forearc basin and trench had formed during this stage, evidence of this subparallel couplet has since disappeared completely.…”
Section: Hp/lt Recrystallization Of the Franciscan Complexmentioning
confidence: 93%
“…Sierra Nevada ranges (Dunne et al 1998;Irwin 2003;Dickinson 2008) reflects an important component of eastward subduction of the Farallon oceanic plate commencing no later than *175 Ma, and continuing until *140 Ma. Underflow also resulted in the generation and storage at depth of HP/LT metamafic rocks, now present as tectonic ± olistostromal blocks in mélanges chiefly of the Franciscan Central Belt (Cloos 1982(Cloos , 1986Wakabayashi et al 2010). Middle and Late Jurassic oceanic plate motion probably involved oblique convergence rather than nearly orthogonal subduction ), because if a major forearc basin and trench had formed during this stage, evidence of this subparallel couplet has since disappeared completely.…”
Section: Hp/lt Recrystallization Of the Franciscan Complexmentioning
confidence: 93%
“…The nearcoastal region of the former forearc broadly coincides with the surface distribution of the serpentinite tectonic blocks and slivers and diapirs in forearc crustal rocks (Figure 2) as well as 'sedimentary' or 'mud' serpentinites that were thought to be part of a mélange of serpentinites erupted on the seafloor in the oceanic basins (Barnes et al 2013), like those observed in some modern subduction zones, such as the Marianas (Fryer et al 1985;Murata et al 2009;Wakabayashi 2011). Field relations in California indicate some of the diapiric or fault-bounded serpentinites were emplaced in the late Cenozoic (Bailey and Everhart 1964;Dickinson 1966;Coleman 1971Coleman , 1977Coleman , 2000Murata et al 1979;Page et al 1999;Wakabayashi 2004Wakabayashi , 2005Wakabayashi , 2012Wakabayashi and Dilek 2011;Wakabayashi et al 2010). The common local occurrence of blocks of mantle peridotite, blueschists, and/or eclogites in such Neogene emplacements suggest that these serpentinite bodies may have originally come from deep crustal and/or mantle depths and were entrained with serpentinite ascent during the formation and lengthening of the San Andreas Fault System.…”
Section: Tectonics Of California Serpentinite In Light Of This Modelmentioning
confidence: 96%
“…Dupuis et al, 2005;Polat and Kerrich, 1999;Saha et al, 2005;Taira et al, 1992;Tankut et al, 1998;Wakabayashi et al, 2010;Xu et al, 2012).…”
mentioning
confidence: 99%